Pathophysiological role of endothelial biomarkers in Bothrops sp. venom-induced renal dysfunction and the therapeutic effect of antivenom - Nicole Coelho Lopes; Gdayllon Cavalcante Meneses; Ranieri Sales de Souza Santos; Leticia Machado de Araújo; Bruna Viana Barroso Martins; Katarina Maria dos Reis Araújo; Valéria Holanda Nogueira de Aquino; Igor Moreira de Almeida; Sandra Mara Brasileiro Mota; Geraldo Bezerra da Silva Junior; Camila Eleuterio Rodrigues; Elizabeth De Francesco Daher; et al. (Toxicon: X)
Snakebite antivenom (SAV) is the standard treatment option to neutralize the toxic effects of snake venom, but their consequences on kidney function need to be better understood. This study aims to evaluate the effects of antivenom on kidney and endothelial biomarkers due to Bothrops venom in two subgroups of patients distinguished by the presence of hemorrhagic syndrome at admission. This prospective study included 34 snakebite patients admitted to a tertiary hospital in Northeast Brazil between August 2019 and November 2020, 50 % of whom experienced spontaneous bleeding. Endothelial and kidney damage biomarkers were analyzed at three time points: before antivenom infusion and after 10 h and 20 h of antivenom infusion. Bleeding patients exhibited higher urine Neutrophil Gelatinase-Associated Lipocalin (uNGAL) and Kidney Injury Molecule-1 (KIM-1) levels, indicating incomplete renal recovery until 20h after antivenom. This group showed higher serum angiopoietin-2 (Ang-2) levels and vascular cell adhesion molecule-1 (VCAM-1). VCAM-1 levels positively correlated with kidney biomarker levels at each time point, especially after SAV. uNGAL was variant across VCAM-1, Ang-1, and Ang-2 levels before antivenom. Elevated levels of uNGAL and KIM-1, observed 10 h after SAV administration, may indicate incomplete renal protection and a potential risk for the development of chronic kidney injury, requiring future follow-up.